The Influence Of Tiktok Social Media On The Social Behavior Of Seventh Grade Student At SMPN 4 Tarogong Kidul - Triyana, Firdaus; Tetep, Tetep; Setiawan, Yana (Indonesian Journal of Social Science Research, 2025)
This study aims to analyze the influence of TikTok use on students' social behavior using a quantitative approach and survey method. The research instrument, a questionnaire, was distributed to students who are active TikTok users. Descriptive analysis shows that TikTok has become part of students' digital routines, used both for entertainment and as a source of information. This platform also encourages creativity, expands social interactions, and makes it easier for students to connect with communities with similar interests. However, the study also found negative impacts such as changes in communication styles, increased imitation of certain trends, disruptions in learning time management, and a tendency to compare themselves with other creators. The research findings indicate that although TikTok appears to influence social behavior descriptively, this influence is not strong enough to be considered statistically significant. Thus, students' social behavior is more influenced by other factors such as family environment, social experiences, and individual character. This study concludes that TikTok has a non-uniform and non-dominant influence on students' social behavior. Therefore, digital literacy efforts and adequate mentoring are needed so that students can utilize TikTok positively and avoid negative impacts that could potentially affect their social and academic development.